Investigation into conventionality of concepts - Navickas, V. (Psichologija, 1995)
The present article represents data on how adults (19-29 year old people including 25 males and 25 females) understand conventionality of concepts “left”/“right”. Results of the investigation indicate that almost a half of subjects do not realize that “left”/“right” is a convention, thinking that “left”/“right” is immanence of objects. The investigation revealed answers of above subjects being analogous to those given by children in various stages of nominal realism (J. Piaget).
Keywords: concepts; conventionality; Piaget